SAHNYA HIBAH DIBAWAH TANGAN BERDASARKAN PUTUSAN PENINJAUAN KEMBALI MAHKAMAH AGUNG REPUBLIK INDONESIA NO.335 PK/Pdt 1987 DI PENGADILAN NEGERI GIANYAR - Ratih Tribuana, Putu Ayu; Rudy, I Dewa Gde (Kertha Semaya : Journal Ilmu Hukum, 2013)
Indonesian Supreme Court Verdict o.335 PK/ Pdt/1987 as dated as 2nd ofSeptember 1989 had granted applicant’s appeal regarding “unauthorized grant”under the consideration of Supreme Court Released Letter No.3 Year 1963 asdated as 5th of September 1963, whereas the document shall not be considered assources of law. Within that, the Released Letter of Indonesian Supreme Court hadimplied firmly that provisions stipulated within Article 1682 BW which obligednotary act for every grant act committed shall be no longer valid according tocurrent law.
Keywords: authentic act, unauthorized act